Big Science: before and after the Manhattan Project - Kragh, Helge (Journal of physics. Conference series, 2024)
Although the concept of Big Science is not well defined, it is often identified with expensive and government-funded post-World-War II projects in physics and space research. However, this definition is too narrow both with regard to chronology and with regard to the sciences in question. Apart from offering some general comments on the notion of Big Science this paper adopts a historical perspective by singling out a few cases of pre-twentieth century Big Science projects in physics and astronomy. These were exceptions, however, and it was only with the Manhattan Project and the early generations of high-energy accelerators that the Big Science era truly started. As argued the development involved new forms of organisation as well as new ethical problems relating to the role and responsibility of the individual scientist.